Parasitic gastro-enteritis (PGE) concurrent with eperythrozoonosis in a goat: a case report - Abdullah, Faez Firdaus Jesse; Adamu, Lawan; Jamal, Mohd Hero Azuan; Osman, Abdinasir Yusuf; Haron, Abdul Wahid; Awang, Dayang Norhaizam; Roslim, Noorashimah (International Organization of Scientific Research, 2013)
A 7 month-old, male Katjang cross goat weighing 35kg with body condition score of 3/5 was presented to Large Animal Ward, University Veterinary Hospital (UVH). The goat had pale mucous membrane and diarrhoea. The goat had moderate normocytic, normochromic anaemia with packed cell volume (PCV) of 0.14 (0.22-0.32) and low normal plasma protein, neutrophilia with left shift and monocytosis, including hyponatraemia, hypocalcaemia and hypoalbuminaemia with increased muscle enzyme (CK). Thin blood film stained with Geimsa showed evidence of blood parasites and mycoplasma sp. 0.1 % of RBC was infected and with high strongyle infestation (13900 epg) using modified McMaster technique. Blood transfusion was done as a result of decreased PCV value to 0.13 on the second day of hospitalization. Parasitic gastro-enteritis (PGE) concurrent with eperythrozoonosis infection was diagnosed in the goat.